1982
DOI: 10.1021/jm00353a010
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid-nucleoside conjugates. 3. Syntheses and preliminary biological evaluation of 1-.beta.-D-arabinofuranosylcytosine 5'-monophosphate-L-1,2-dipalmitin and selected 1-.beta.-D-arabinofuranosylcytosine 5'-diphosphate-L-1,2-diacylglycerols

Abstract: Several new phospholipid-ara-C conjugates have been prepared and tested as prodrugs of the parent ara-C. The new derivative include ara-CMP-L-dipalmitin, ara-CDP-L-distearin, ara-CDP-L dimyristin, ara-CDP-L-diolein, and the radioactively labeled derivative ara-CDP-L-di[1-14C]palmitin. In addition, the unusually stable ara-CMP-L-dipalmitin-N-phosphoryldicyclohexylurea adduct was isolated as a crystalline solid (two diastereomers) in the reaction sequence to prepare ara-CMP-L-dipalmitin. The new prodrugs were so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…In some later studies, Ryu et al developed more synthetic schemes for using diacylglycerols with different aliphatic chain lengths attached to ara-C monophosphate or ara-C diphosphate [62]. The new synthetic scheme for the synthesis of a conjugate with only one phosphate required the protection of ara-C using levulinic acid protecting groups.…”
Section: Phospholipid Ara-c Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In some later studies, Ryu et al developed more synthetic schemes for using diacylglycerols with different aliphatic chain lengths attached to ara-C monophosphate or ara-C diphosphate [62]. The new synthetic scheme for the synthesis of a conjugate with only one phosphate required the protection of ara-C using levulinic acid protecting groups.…”
Section: Phospholipid Ara-c Conjugatesmentioning
confidence: 99%
“…Previous investigators have had many successes with phospholipid/nucleoside analog conjugates; however, there are still improvements that can be made to these compounds [59,60,[62][63][64]73]. In our laboratory, we focused on the synthesis of a thioether phospholipid (1-S-dodecyl-2-Odecyl-thioglycero-3-phosphatidic acid) conjugated to either gemcitabine or ara-C [75].…”
Section: Phospholipid Gemcitabine and Ara-c Conjugatesmentioning
confidence: 99%
“…Several independent researchers have also tried to address these drawbacks of Cyt by synthesizing its various prodrugs, [26][27][28][29] analogues 30 and conjugates. [31][32][33][34][35][36][37] Phospholipid-Ara-C conjugates were prepared as a prodrug of Cyt and found to be much more effective than Ara-C in vivo. 31 Conjugate of thioether phospholipid with Cyt showed stability in a micellar solution and offered substantial therapeutic benefit to mice with leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] Phospholipid-Ara-C conjugates were prepared as a prodrug of Cyt and found to be much more effective than Ara-C in vivo. 31 Conjugate of thioether phospholipid with Cyt showed stability in a micellar solution and offered substantial therapeutic benefit to mice with leukemia. 32 Fatty acyl derivatives of Cyt were developed to improve cellular uptake.…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks of nucleoside therapeutics provoke a profound interest in the search of prodrugs exhibiting an effectiveness superior to that of the parent drug. Among such derivatives, conjugates of nucleosides and phospholipids attracted attention and it was demonstrated that these derivatives display advantageous biological properties over free nucleosides (Ryu et al 1982;Shuto et al 1995;Vodovozova et al 1996;Herrmann et al 1997;Brachwitz et al 1998Brachwitz et al , 1999Kucera et al 1998;Mavromoustakos et al 2001;Alexander et al 2003; for a review, see Morris-Natschke et al 2003).…”
Section: Introductionmentioning
confidence: 99%